Enhancement of mechanical and rheological properties of PA-12 through silane modification - Jadhav, V. Pravin; Mahajan, Digvijay; Patil, Prashant; Umbarkar, Shubhangi B.; Pol, Harshawardhan (Bulletin of Materials Science, 2025)
This research examines the effects of silane modifications on polyamide 12 (PA-12) to improve its mechanical and thermal properties. The study employs a reactive extrusion technique to integrate various silanes-Dynasylan (R) AMEO, Dynasylan (R) 1189, Dynasylan (R) DAMO and Dynasylan (R) VPS 4721-at different concentrations (0.25, 0.5 and 0.75%). Key findings reveal that silane modifications significantly enhance the tensile strength, impact resistance and viscoelastic behaviour of PA-12, with the Dynasylan (R) DAMO formulation achieving the highest tensile strength of 38.25 MPa vis-& agrave;-vis 8.02 MPa for PA-12. The modifications also resulted in a reduction of crystallinity by over 35%, contributing to improved toughness and impact strength. Rheological assessments indicate that the flow properties of PA-12 are positively altered, enhancing its complex viscosity and storage modulus, which are crucial for applications in automotive and aerospace industries. Thermal analysis through differential scanning calorimetry and thermogravimetric analysis confirms improved thermal stability, particularly in the 0.5% Dynasylan (R) AMEO-modified sample, exhibiting an onset temperature of 421.87 degrees C. The study emphasizes the importance of the silane type and dosage in tailoring PA-12's performance for advanced applications, suggesting future research directions to further refine silane-modification techniques for enhanced polymer performance. This research provides valuable insights into polymer-modification strategies, highlighting the potential for silane treatments to optimize the mechanical, thermal and rheological properties of PA-12 for diverse industrial applications.
Keywords: mechanical properties; Polyamide 12 (PA-12); reactive extrusion; rheological behaviour; silane modification; thermal stability

Steric-bulk directed polymerization of ethylene to disentangled ultra-high molecular weight polyethylene - V. Bodkhe, Dnyaneshwar; Patel, Ketan; Shaikh, Maulali H.; Kaulage, Sandeep H.; Mahajan, Digvijay; Pol, V. Harshawardhan; Chikkali, Samir H. (European Polymer Journal, 2026)
{The electron-withdrawing pentafluorophenyl phenoxy-imine-derived titanium complexes are known to produce ultrahigh molecular weight polyethylene (UHMWPE). However, cyclohexyl phenoxy-imine-derived zirconium complexes have been reported to produce low molecular weight polyethylene. The disparity between the two types of polyethylenes and the two types of catalysts can be bridged if a titanium complex bearing sterically bulky groups is made to produce UHMWPE. We report steric bulk-directed cyclohexyl phenoxy-imine titaniumcatalyzed synthesis of UHMWPE in a disentangled state. The influence of steric bulk in a phenoxy-imine-cyclohexyl ligand framework on titanium complex formation and subsequent ethylene polymerization was investigated through a combined computational and experimental approach. Density functional theory (DFT) and buried volume analyses indicated that increasing steric demand from -H to -Me to -tert-Bu substituents enhances the buried volume around the metal center, potentially favoring high molecular weight polyethylene formation. Guided by these insights, three ligands, L1-L3, were synthesized in excellent yields and fully characterized, including by single-crystal X-ray diffraction. Treatment of L1-L3 with a titanium precursor produced respective complexes, Cat.1-Cat.3, in good yields. These were characterized by NMR, IR, MS, and single-crystal X-ray diffraction. Upon activation with various co-catalysts [methyl aluminoxane (MMAO), triisobutylaluminum (TIBA), and tetrakis (pentafluoro phenyl) borate (BT)], these complexes initiated ethylene polymerizations. The catalytic activity increased from Cat.1 to Cat.2 with growing steric bulk, but decreased for the highly hindered Cat.3, likely due to restricted monomer access to the active site. Among the three, Cat.2, in combination with MMAO, showed the best performance under optimized conditions and produced ultrahigh molecular weight polyethylene (UHMWPE
Keywords: Metal catalysis; Phenoxy-imine ligand; Polyethylene; Titanium complexes; uHMWPE